METHODOLOGY FOR BUILDING DISTRIBUTED CONTROL SYSTEM FOR TELECOMMUNICATION NETWORKS BASED ON CORBA TECHNOLOGY - Valery P. Mochalov; Sergey V. Yakovlev; Natalia Yu. Bratchenko (Вестник Северо-Кавказского федерального университета, 2022)
The article offers a description of methodology for building a distributed system for managing communication networks based on the CORBA technology. There is a view on the functional components of the CORBA environment. The formalism of Petri colour nets was used here to develop a model for integrating programme components.